Games and Learning Alliance : Third International Conference, GALA 2014, Bucharest, Romania, July 2-4, 2014, Revised Selected Papers - De Gloria, Alessandro; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the refereed proceedings of the Third International Conference on Games and Learning Alliance, GALA 2014, held in Bucharest, Romania, in July 2014. The 15 revised papers presented were carefully reviewed and selected from 26 submissions. The papers presented cover a variety of aspects and knowledge fields. They are grouped into four sessions: pedagogy, technology, design, and applications.
Beyond serious games -- Investigating the deployment of serious games in formal education -- Understanding the role of the teacher in using a serious game -- Identifying pedagogical uses of serious games -- Multiplayer serious games and user experience -- A brief practical game development approach -- Gamification in a smart city context -- A conceptual model towards in the scaffolding of learning experience.
Keywords: Computer science; Education; Artificial intelligence; Personal Computing; Computers and Education; Artificial Intelligence; Information Systems Applications (incl. Internet).; User Interfaces and Human Computer Interaction; Computers and Society